Foramen magnum meningiomas: surgical treatment in a single public institution in a developing country - Benedicto Oscar Colli; Carlos Gilberto Carlotti Junior; João Alberto Assirati Junior; Luis Alencar Biurrum Borba; Vicente de Paulo Martins Coelho Junior; Luciano Neder (Arquivos de Neuro-Psiquiatria)
Objective: To analyze the clinical outcome of patients with foramen magnum (FM) meningiomas. Method: Thirteen patients (11 Feminine / 2 Masculine with FM meningiomas operated on through lateral suboccipital approach were studied. Clinical outcome were analyzed using survival (SC) and recurrence-free survival curves (RFSC). Results: All tumors were World Health Organization grade I. Total, subtotal and partial resections were acchieved in 69.2%, 23.1% and 7.7%, respectively, and SC was better for males and RFSC for females. Tumor location, extent of resection and involvement of vertebral artery/lower cranial nerves did not influence SC and RFSC. Recurrence rate was 7.7%. Operative mortality was 0. Main complications were transient (38.5%) and permanent (7.7%) lower cranial nerve deficits, cerebrospinal fluid fistula (30.8%), and transient and permanent respiratory difficulties in 7.7% each. Conclusions: FM meningiomas can be adequately treated in public hospitals in developing countries if a multidisciplinary team is available for managing postoperative lower cranial nerve deficits.